Familial articular chondrocalcinosis in Spain. Issue 7 (July 1990) - Balsa, A; Martín-Mola, E; Gonzalez, T; Cruz, A; Ojeda, S; Gijón-Baños, J
Abstract : One hundred and one first degree relatives of 35 patients with chondrocalcinosis were examined for the presence of familial disease. Eleven subjects from nine families showed radiological chondrocalcinosis, a prevalence of familial disease of 26%. Two different patterns of disease were noted--the older generation was more commonly affected, and the younger generation and second degree relatives were exempt. Clinical and radiological differences were found between the early and late onset groups, but not between late onset and sporadic forms of chondrocalcinosis. These findings support the suggestion that the true prevalence of familial disease. is underestimated. A dominant, autosomal transmission with variable penetrance is consistent with our findings, which suggests that homozygous patients with familial chondrocalcinosis may present a more severe form of the disease.